Komposisi Hasil Tangkapan Jaring Insang (Gill Net) di Perairan Krueng Raya, Aceh Besar, Provinsi Aceh - Aldo R.F. Coheny; Edy Miswar; Rian Juanda (Jurnal Ilmiah Mahasiswa Kelautan Perikanan Unsyiah, 2018)
ABSTRACT       Krueng Raya water is one area that is located in Aceh Besar District where the gill nets were widely used by Fisherman. The utilization of gill nets in Krueng Raya was still traditional. The fisherman usually performs the operation catching up on the day and the night. The information about composition of the catch in gill nets which are operated at night and during the day in Krueng Raya was still limited, but that pieces of information is urgently needed for the development of more advanced gill nets in Krueng Raya This study aims to know the composition, size, diversity, and dominance of the gill net catches in Krueng Raya. Composition and size of catches were analyzed in descriptive, the diversity was analyzed using the Shannon-Wienerindex, while dominance was analyzed using the Odum dominance index. Descriptive analysis showed that the largest composition of catches in gill nets that operating during the day was yellowtail fish(19.6%) and the least was whitetip shark(0.4%) and in gill nets that operating in the night, the largest composition of catches was queenfish(27.7%) and the least was scup fish (0.5%). Size of catches are the most often caught in gill nets that operating during the day was 21.28-25.03 cm  (160 unit of fish or 35.4%) and in gill nets that operating in the night was 34.20-41.14 cm (119 unit of fish or 30.2%). The results of the diversity and dominance analysis showed that the diversity index of catches in gill nets that operating in the day and in the night were in medium category (2.17/1.93) and the dominance index of catches in gill nets that operating in the day and in the night was in the low category (0.14/0.20).Keywords: Gill nets, Catches, Diversity index, Dominance index ABSTRAK       Perairan Krueng Raya merupakan salah satu daerah yang terletak di Kabupaten Aceh Besar dimana alat tangkap jaring insang banyak digunakan di kalangan nelayannya. Penggunaan alat tangkap jaring insang di Perairan Krueng Raya terbilang masih sederhana. Nelayan jaring insang biasanya melakukan operasi penangkapan pada siang dan malam hari. Informasi mengenai jenis hasil tangkapan jaring insang yang dioperasikan pada malam dan siang hari di Perairan Krueng Raya secara umum masih sangat terbatas, akan tetapi informasi tersebut sangat dibutuhkan untuk pengembangan jaring insang yang lebih maju di Perairan Krueng Raya. Penelitian ini bertujuan untuk mengetahui komposisi, ukuran, keanekaragaman serta dominansi hasil tangkapan jaring insang di Perairan Krueng Raya. Komposisi dan ukuran hasil tangkapan dianalisis secara deskriptif, keanekaragaman dianalisis dengan menggunakan Indeks Shannon-Wiener, sedangkan dominansi dianalisis dengan menggunakan indeks dominansi Odum. Hasil analisis deskriptif menunjukkan bahwa komposisi hasil tangkapan jaring insang siang yang paling banyak tertangkap adalah ikan ekor kuning (19,6%) dan yang paing sedikit adalah ikan hiu (0,4%), sedangkan pada jaring insang malam yang paling banyak tertangkap adalah ikan talang (27,7%) dan yang paling sedikit adalah ikan jarang gigi (0,5%). Ukuran hasil tangkapan yang paling sering tertangkap pada jaring insang siang adalah 21,28-25,03 cm sebanyak 160 ekor (35,4%) dan pada jaring insang malam adalah 34,20-41,14 cm sebanyak 119 ekor (30,2%). Hasil analisis keanekaragaman dominansi menunjukkan bahwa indeks keanekaragaman hasil tangkapan jaring insang berada pada kategori sedang baik siang ataupun malam hari (2,17/1,93), sedangkan indeks dominansi berada pada kategori rendah baik siang ataupun malam hari (0,14/0,20).Kata Kunci: Jaring insang, Hasil tangkapan, Indeks keanekaragaman, Indeksdominansi